Assessing matK AND ITS2 DNA Barcodes for Identifying Hibiscus rosa-sinensis Morphological Variants - Seow, Yee Loon (2017)
A major problem in conversation and ecological studies is the limited of taxonomists available to identify the vast numbers of flora and fauna, amongst them the abundant and globally distributed Hibiscus species. In this study, the discriminant analysis of morphological traits of Hibiscus species also revealed the important of floral characteristics in distinguishing between species in this genus as well as subspecies, and the difficulty of identification in the absence of flowers. Hence, DNA barcoding is a potential tool to overcome the burden of the taxonomists and provide a rapid detection to be used by non-taxonomists. ITS2 and matK were tested for the identification of Hibiscus rosa-sinensis variants, together with Hibiscus schizopetalus. After plant DNA was extracted from leaves, the barcode loci was amplified, sequenced and the data analysed.Despite the good quality genomic DNA extracted, only matK PCR product had sequences of good quality. BLAST analysis yielded ambiguous identification perhaps due to requirement to re-examine the separation of genus in this taxon. The best fit nucleotide substitution model was T92 model instead of the widely used K2P model which was probably due to unequal bases frequencies (A≠T≠G≠C). The phylogenetic trees were able to distinguish between Hibiscus rosa-sinensis and Hibiscus schizopetalis, but not the morphological variants. However, the data complemented morphological identification in the absence of flowers indicating that molecular data including other loci could contribute to identification and the thus studies and management of species diversity.